2018
DOI: 10.1371/journal.pone.0208103
|View full text |Cite
|
Sign up to set email alerts
|

Cereal aphids differently affect benzoxazinoid levels in durum wheat

Abstract: Aphids are major pests in cereal crops that cause direct and indirect damage leading to yield reduction. Despite the fact that wheat provides 20% of the world’s caloric and protein diet, its metabolic responses to aphid attack, in general, and specifically its production of benzoxazinoid defense compounds are poorly understood. The objective of this study was to compare the metabolic diversity of durum wheat seedlings (Triticum turgidum ssp. durum) under attack by three different cereal aphids: i) the English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 63 publications
2
25
0
2
Order By: Relevance
“…Then, the frozen powder was weighed, and the 1:10 (w: v) ratio of extraction solvent contained 80% methanol (0.1% formic acid). The mix was vortexed briefly; then, the tubes were shaken for 40 min at 4°C and centrifuged for 5 min at 14,000 g. Filtration was performed by centrifuging the samples on a 0.22-μm filter plate (EMD Millipore Corp., Billerica, MA, USA) at 3000 g for 5 min [74,110,111]. The extracted mixtures were covered with a WebSeal Mat and kept at 10°C.…”
Section: Benzoxazinoid Extraction Analysis and Identificationmentioning
confidence: 99%
“…Then, the frozen powder was weighed, and the 1:10 (w: v) ratio of extraction solvent contained 80% methanol (0.1% formic acid). The mix was vortexed briefly; then, the tubes were shaken for 40 min at 4°C and centrifuged for 5 min at 14,000 g. Filtration was performed by centrifuging the samples on a 0.22-μm filter plate (EMD Millipore Corp., Billerica, MA, USA) at 3000 g for 5 min [74,110,111]. The extracted mixtures were covered with a WebSeal Mat and kept at 10°C.…”
Section: Benzoxazinoid Extraction Analysis and Identificationmentioning
confidence: 99%
“…Metabolic profiling via GC/MS was performed to study the metabolic fluxes in response to insect attack and showed an enhanced synthesis of GABA and glyoxylate, which offers resistance against brown planthopper [186]. In another study, rice metabolomics analysis was executed to study the resistance against Chilo suppressalis and aphid resistance in wheat [187,188]. Weeds are also considered as destructive pests for crop yield reduction.…”
Section: Elucidation Of Biotic Stress Resistance In Plantsmentioning
confidence: 99%
“…Then, the frozen powder was weighed, and the 1:10 (w:v) ratio of extraction solvent contained 80% methanol (0.1% formic acid). The mix was vortexed briefly; then, the tubes were shaken for 40 min at 4 °C and centrifuged for 5 min at 17,000 g. Filtration was performed by centrifuging the samples on a 22-μm filter plate (EMD Millipore Corp., Billerica, MA, USA) at 3,000 g for 5 min [74, 110,111]. The extracted mixtures were covered with a WebSeal Mat and kept at 10 °C.…”
Section: Benzoxazinoid Extraction Analysis and Identificationmentioning
confidence: 99%